Hypothetical Model of Religious Character Education Based on Local Wisdom in the Indigenous Community - Darisman, Dede; Nurdin, Encep Syarief; Kosasih, Aceng; Nurbayani K, Siti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The purpose of this study is to explore a hypothetical model of religious character education based on the local wisdom of the Kuta Ciamis Indigenous Community by identifying: 1) Religious Core Values, 2) Value Internalization Methods, and 3) Dimensions of Character Education. This study employs a qualitative approach, utilizing ethnographic methods. The research data sources comprise both primary and secondary data, with data collection techniques including in-depth interviews with key informants, such as Traditional Leaders, Elders, Kuncen, and Youth Activists. Participatory observation by observing the socio-religious life of the Kuta Ciamis Indigenous Community, as well as documentation studies used by researchers, including community profile documents of Kuta Village, and archives of data on activities of the Kuta Ciamis Indigenous Community. Data analysis was conducted through reduction, data display, and conclusion. The results of the study show that: 1) the hypothetical model of religious character education is built on three main foundations of core values, namely, religious (monotheism, worship, morals), cultural (rituals, symbols, taboos), and socio-ecological (harmonious relationships between humans and others and nature). 2) Internalization and enculturation of contextual values, with the important role of families, traditional figures, religious figures, and social communities in shaping religious character. Religious values ​​are internalized through role models, habituation, social control, and cultural narratives such as myths and ancestral wisdom. This model produces a holistic religious character that unites spiritual, moral, social, and ecological piety. Methodologically, this model confirms the effectiveness of community-based character education and local culture as an alternative paradigm for contextual and sustainable national character education. 3) The four main dimensions of religious character formation based on local wisdom are: spiritual, social, moral, and ecological.